Divalent cannabinoid-1 receptor ligands: A linker attachment point survey of SR141716A for development of high-affinity CB1R molecular probes. Issue 21 (1st November 2019) - Grant, Phillip S.; Kahlcke, Nils; Govindpani, Karan; Hunter, Morag; MacDonald, Christa; Brimble, Margaret A.; Glass, Michelle; Furkert, Daniel P.
Graphical abstract: Abstract: The cannabinoid-1 receptor (CB1R) inverse agonist SR141716A has proven useful for study of the endocannabinoid system, including development of divalent CB1R ligands possessing a second functional motif attached via a linker unit. These have predominantly employed the C3 position of the central pyrazole ring for linker attachment. Despite this precedent, a novel series of C3-linked CB1R-D2R divalent ligands exhibited extremely high affinity at the D2R, but only poor affinity for the CB1R. A systematic linker attachment point survey of the SR141716A pharmacophore was therefore undertaken, establishing the C5 position as the optimal site for linker conjugation. This linker attachment survey enabled the identification of a novel divalent ligand as a lead compound to inform ongoing development of high-affinity CB1R molecular probes.